Ageism towards older and younger people in the wake of the COVID-19 outbreak. (March 2022) - Werner, Perla; AboJabel, Hanan; Tur-Sinai, Aviad
Highlights: COVID-19 elicited ageist attitudes towards younger and older people. We found significantly higher levels of COVID-19 ageism towards younger than older people. Age stereotypes play a major role in both types of ageism. Public and scientific media should spread messages aimed at reducing both types of ageism. Abstract: Objectives: The COVID-19 pandemic has provided a rich environment for ageist attitudes towards both older and younger people. However, publications on ageism during the outbreak have been mostly non-empirical and have concentrated on ageist beliefs directed towards older people. To overcome these limitations, we examined empirically the prevalence and the determinants of ageism towards older and younger people in the wake of COVID-19. Study design: A cross-sectional study using an online survey was conducted with 503 Israeli adults (51.9% male, 79.5% Jews, mean age 47 years). Main measures: We used a structured questionnaire that measured the following: COVID-19 ageism towards older people, COVID-19 ageism towards younger people, stereotyping, the experience of discrimination, perceived fears about contracting COVID-19, subjective knowledge about COVID-19, and sociodemographic characteristics. Results: Overall, participants reported a relatively low level of COVID-19 ageism towards older people but a significantly higher level of COVID-19 ageism towards younger people. Hierarchical regressions revealed that negative age stereotypes were the most important determinants of both types of ageism. Sociodemographic variables (including age and majority/minority) were significant determinants only for COVID-19 ageism towards older people. That is, older and Jewish participants reported lower levels of this type of ageism. Conclusions: Our findings demonstrate that negative age-related stereotypes have played a central role in ageist beliefs towards both older and younger people during the COVID-19 crisis. It is recommended that the public and scientific media start disseminating messages aimed at reducing rather than increasing negative stereotypes directed towards younger and older people.